Effects of amino acid intake on anabolic processes - Wolfe, R. R. (Canadian Journal of Applied Physiology, 2001)
In the resting state muscle protein breakdown exceeds the rate of muscle protein synthesis, meaning that the balance between synthesis and breakdown is negative. Resistance exercise improves the net balance by stimulating muscle protein synthesis, but nutrient intake is required for synthesis to exceed breakdown (i.e., an anabolic response). Exercise and exogenous amino acids have an additive effect on muscle protein synthesis. There is a time-course of the response to a steady-state change in amino acid concentration. The signal for stimulation of muscle protein synthesis appears to be the extracellular concentrations of one or more of the essential amino acids (EAAs). Further, the rate, and direction, of change in extracellular concentrations (rather than the static concentration, per se) may be the important. Ingestion of non-essential AAs is not needed to stimulate muscle protein synthesis. Carbohydrate has, at most, a modest effect to enhance the response to amino acid ingestion after exercise. Finally, a mixture of EAAs + CHO more effectively stimulates muscle protein synthesis when taken before as opposed to after exercise.